Pencetakan Al-Qur’an, Isu Gender, dan Komodifikasi Agama: - Fairuzah, Fairuzah; Nadhiroh, Wardatun; Fathurrosyid, Fathurrosyid (SUHUF, 2024)
The Mushaf for Muslimah printing, an innovation in religious publishing in Indonesia, has garnered attention for presenting the Qur’an with translations and content markers adapted explicitly for women. This research aims to investigate the potential of this publication as an agent of women’s empowerment in the religious context while also exploring the challenges and risks associated with patriarchal ideology and the commodification of religion. Through the theoretical frameworks of religious commodification and feminism, this study will analyze how Mushaf for Muslimah uses religious symbols as commodities and responds to gender issues inherent within it. This research is a case study with primary data collected through observation, documentation, and interviews with the publisher, subsequently analyzed using content analysis approaches. In the context of commodification and feminist theories, this research identifies the complexities in efforts to empower women through religion while highlighting the challenges in maintaining a balance between the sacredness of religion and gender inclusion. These findings enrich our understanding of the dynamics of contemporary Qur’anic printing and the role of religion in shaping gender identities and roles in society.